The control loop cardiorhythm organism of girls with atopic dermatitis in Stavropol - Olga Alekseevna Butova; Anastasia Viktorovna Chursina (Наука. Инновации. Технологии)
At the conditions of physiological dormancy with atopic dermatitis in the reg-ulation of heart rate leading is the 3rd level of the central loop, characterized by the dominance of the sympathetic modulation performance of stress test results in connection 2nd level of the central loop, indicating cerebral ergotrop influence and emotional stress.